Dynamic buckling instabilities in fluids and solids - Kodio, O (2019)
Many natural phenomena encountered in nature may be understood through the paradigm of buckling instability. Examples include the design of columns in structural engineering, the folding of geological formations, the collapse of blood vessels, and the fragmentation of uncooked spaghetti, to name only a few. The phenomenon of buckling has traditionally been seen only as a nuisance, but more recently it has also proven useful as a potential tool for pattern formation, particularly at small scales. Many studies have focused on the features of static buckling, particularly pattern formation.